On the Treatment of a Dirichlet–Neumann Mixed Boundary Value Problem for Harmonic Functions by an Integral Equation Method - González, R.; Kress, R. (SIAM journal on mathematical analysis, 1977)
Using an approach which extends the well-known classical integral equation methods, we reduce a mixed boundary value problem for harmonic functions to a system consisting of two integral equations of the second kind. Existence is proved by the Fredholm alternative for compact operators. The integral equations can be solved apptgximately by successive iterations. Further investigations are made on the spectrum of the boundary integral operator.